2020
DOI: 10.1177/1539449220920732
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Yonsei-Bilateral Activity Test (Y-BAT)-Bilateral Upper Extremity Inventory Using Rasch Analysis

Abstract: There is little assessment to provide specific information about quality of bilateral upper extremity movement specifically. This study examined the psychometric properties of the Yonsei-Bilateral Activity Test (Y-BAT). An observational cross-sectional design was used with 100 stroke survivors. Unidimensionality was examined using factor analyses, and Rasch analysis was used to test rating scale structure, fit statistics, and precision of the Y-BAT. The Y-BAT demonstrated a unidimensional measurement construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Furthermore, we found that there were two groups of items with a similar difficulty level, namely, Item CS09 (overhand throwing; 1.97 logits) and Item CS14 (kicking; 1.95 logits), as well as Item CS13 (longitudinal roll; 0.18 logits) and Item CS05 (crawling; 0.15 logits). Other research proposes that similar difficulty levels of test items may not provide more calibration information for evaluating movement skills [ 44 ]. The best solution was to delete some of the items of the same difficulty levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, we found that there were two groups of items with a similar difficulty level, namely, Item CS09 (overhand throwing; 1.97 logits) and Item CS14 (kicking; 1.95 logits), as well as Item CS13 (longitudinal roll; 0.18 logits) and Item CS05 (crawling; 0.15 logits). Other research proposes that similar difficulty levels of test items may not provide more calibration information for evaluating movement skills [ 44 ]. The best solution was to delete some of the items of the same difficulty levels.…”
Section: Discussionmentioning
confidence: 99%
“…The best solution was to delete some of the items of the same difficulty levels. Determining whether to delete items has often been used as the internal consistency coefficient: If the internal consistency coefficient is too high (i.e., Cronbach's alpha was greater than 0.98), item redundancies are suggested [ 44 ] and it is considered necessary to delete some items. In this study, the internal consistency coefficient of the CMSQ was only 0.80; thus, we did not delete any items.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We referred to Facets guidelines and adopted MnSq values between 0.7 and 1.3 for acceptable criteria in this study ( 35 , 36 ). The intraclass correlation coefficient (ICC) was used to examine the rater's retest reliability ( 37 ). Wikstrom recommends the following criteria for ICC: scores of 0.9–1.0 for excellent; 0.80–0.89 for good; 0.7–0.79 for fair; and below 0.69 for poor ( 38 ).…”
Section: Methodsmentioning
confidence: 99%